Oktawian Jeleński – a Pole in a Tsar’s Uniform. On Russians and Polish-Russian Relations in the 19th Century - Caban, Wiesław (Respectus Philologicus, 2018)
[full article in Polish; abstract in English] In his memoirs of a Pole, Oktawian Jeleński presented the life of soldiers, gentry, peasants, merchants, Russian women and Orthodox clergy in provinces. He also focused on Polish-Russian relations during the January Uprising. His observations deserve attention of the historians researching Polish-Russian relations in the 19th century. Without doubt, Jeleński supported conciliatory approaches, however, at the same time he would severely criticise actions of the Russian administration and police undertaken in order to weaken the Polish spirit, especially in the North-Western Krai. Jelenski believed that good Polish-Russian relations were possible to achieve. In his opinion, however, the Russian „patriotic historiography” and propaganda practiced by Moskowskije wiedomosti, whose editor was Mikhail Katkov, stood in the way. Jeleński’s memoirs are a clear demonstration that a Pole wearing a Tsar’s uniform did not have to deny his Polish identity and the Catholic religion.